RADIO: YESTERDAY, TODAY AND TOMORROW - Ahmedov, Azimjon Ilhomovich; Qobulov, Isomiddin Sodiqjon o‘g‘li (Educational Research in Universal Sciences, 2023)
This article provide information about the history of radio, its present status today, and future development.